2019
DOI: 10.1038/s41598-019-39406-9
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of the East-Central-South-African genotype of Chikungunya virus in Brazil and the city of Rio de Janeiro may have occurred years before surveillance detection

Abstract: Brazil, which is hyperendemic for dengue virus (DENV), has had recent Zika (ZIKV) and (CHIKV) Chikungunya virus outbreaks. Since March 2016, CHIKV is the arbovirus infection most frequently diagnosed in Rio de Janeiro. In the analysis of 1835 syndromic patients, screened by real time RT-PCR, 56.4% of the cases were attributed to CHIKV, 29.6% to ZIKV, and 14.1% to DENV-4. Sequence analyses of CHIKV from sixteen samples revealed that the East-Central-South-African … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 31 publications
3
48
1
3
Order By: Relevance
“…Despite the reports indicating that the introduction of the ECSA genotype was in Brazil in 2014, a recent study showed that this genotype has been circulating in Brazil since 2013, almost a year before it was detected in humans [56]. This highlights the role of entomological surveillance, as the virus may be circulating silently, before human infections may be detected.…”
Section: Discussionmentioning
confidence: 95%
“…Despite the reports indicating that the introduction of the ECSA genotype was in Brazil in 2014, a recent study showed that this genotype has been circulating in Brazil since 2013, almost a year before it was detected in humans [56]. This highlights the role of entomological surveillance, as the virus may be circulating silently, before human infections may be detected.…”
Section: Discussionmentioning
confidence: 95%
“…Another potential explanation for the higher prevalence among women during the study period was the emergence of Chikungunya virus at the time, whose chronic stage is often accompanied by severe pain, especially among women (Souza et al, 2018) and yet may be under-detected and treated by the healthcare system (Bagno et al, 2019). The complex interrelationship of an ongoing Chikungunya epidemic, which dates back to 2013 (Souza et al, 2019) with the medical and non-medical use of opioids remain to be fully discerned.…”
Section: Discussionmentioning
confidence: 99%
“…PR technology with high inactivation capacity is particularly important to safeguard the blood supply in areas impacted by emerging arboviruses. Not only such viruses can emerge in the human population months to years before surveillance detects them, but most infections are commonly asymptomatic . In 45% of the YF cases, symptoms may develop 3 to 6 days after infection.…”
Section: Discussionmentioning
confidence: 99%